IMPLEMENTASI PSAK 107 MELALUI PELAYANAN GADAI EMAS SYARIAH PADA BANK SYARIAH MANDIRI SURABAYA - Siti Mahmudah (Behavioral Accounting Journal, 2020)
Sharia banking from time to time has experienced an increase in both the number of customers and savings or financing products. An example of a sharia banking product is the Sharia gold pawn which is implemented by Bank Syariah Mandiri Surabaya. Gold is jewelry that has a high resale value, even if the value decreases, it doesn't drop too much. Gold can be in the form of necklaces, rings, bracelets, pendants and so on with different carats and weights. Gold pawning is a process for obtaining loan funds using economical and valuable items as collateral. If later the payment is paid, the goods will be returned in full, for this purpose maintenance costs are required, namely ujroh, which is paid every 4 months. To carry out a Sharia gold pawn, an ijarah contract is used, which is a trial fee or maintenance service fee because the party receiving the pawn is responsible for the existence of the goods being pawned. Service at Bank Syariah Mandiri Surabaya is very fast, straightforward, friendly, and has clear information about the financing we take.